Die geographische und familiäre Herkunft der Ordensgebietiger Konrad von Kyburg und Rudolf von Kyburg - Gotowko, Piotr (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
The geographical and familial origins of the Teutonic Order’s officials Konrad von Kyburg and Rudolf von Kyburg The researchers of the Teutonic Order have placed the brethren Konrad (before 1336 – 12. April 1402) and Rudolf (before 1337–1404) von Kyburg in the north-eastern part of present-day Switzerland – either in the castle of Kyburg near Winterthur in the eastern Canton of Zurich, or in the Canton of Turgovia, lying in the East of Canton Zurich and to the South of Lake Bodensee. Their family lost those areas by 1265, after a sudden death of Hartmann V von Kyburg (1263) and the childless death of his uncle, Hartmann IV (1264). The only successor, the minor daughter of Hartmann V, Anna von Kyburg, was not able to keep her inheritance, which was quickly taken by her nephew Rudolf IV von Habsburg, latter known as German King Rudolf I. He arranged a marriage between Anna and his relative, Eberhard von Habsburg-Laufenburg, leaving them only Burgdorf and Thun in the nowadays Canton Berne. Their son, Hartmann, had taken the name of the maternal dynasty, calling himself since 1297 Hartmann I von Kyburg. His son, Eberhard II von Kyburg, succeeded him. He was the father of eleven children with Konrad von Kyburg and Rudolf von Kyburg among them. Despite their name, they came from Burgdorf and had joined the Teutonic Order because the poor parents could not guarantee them a subsistence. The carreer of Konrad von Kyburg started in the late 1380s. In 1392 he was promoted to the Comtur of Balga and from 1396–1402 had even reached the high rank of the Great Hospitaller. The carrier of his younger brother, Rudolf, was less impressive for he became 1391–1402 the Comtur of Rehden.